SELECTIVE ATENOLOL DETERMINATION IN BLOOD USING MOLECULAR IMPRINTED POLYMER WITH ITACONIC ACID AS FUNCTIONAL MONOMER - Hasanah, Aliya Nur; Yulianti, Asri Budi; Rahayu, Driyanti (International Journal of Applied Pharmaceutics, 2019)
Objective: This study was aimed to determine analytical performance and physical character of MI-SPE (Molecular Imprinted Solid Phase Extraction) atenolol using itaconic acid as the functional monomer and to implement the material for the extraction of atenolol in blood serum. Methods: This experiment was performed by determining association constants between monomer-template with UV-Vis spectrophotometer, the synthesis of MI-SPE atenolol using bulk polymerization method, template extraction, evaluation of the adsorption ability and capacity of sorbent, evaluation of sorbent selectivity, and determining their physical character using Fourier Transform Infrared (FTIR) and Scanning Electron Microscope (SEM). In the end, the sorbent then was implemented to extract atenolol in blood serum. Results: Analytical performance showed that MI-SPE sorbent has Imprinting Factor (IF) 10.632 which is the largest number compared to IF when using another beta blocker compound. Physical characterization obtained by MI-SPE using Scanning Electron Microscope (SEM) method showed that MI-SPE morphology has homogeneous pore and number of cavities than its blank. MI-SPE has recovery percentage 92.22 % atenolol when it applied to blood serum spiked with atenolol standard. Conclusion: MI-SPE sorbent made from the itaconic acid monomer in methanol porogen potential to be used for the extraction of atenolol from the blood sample by selectively bind to atenolol.